CD19+CD24hiCD38hi B Cell Dysfunction in Primary Biliary Cholangitis. (10th February 2020) - Chen, Qubo; Lai, Lanmin; Chi, Xiaoling; Lu, Xinyi; Wu, Huaxian; Sun, Jing; Wu, Weilin; Cai, Li; Zeng, Xuan; Wang, Chuyang; Chen, WeiCheng; Peng, Anping
Abstract : CD19 + CD24 hi CD38 hi B cells are immature transitional B cells that, in normal individuals, exert suppressive effects by IL-10 production but are quantitatively altered and/or functionally impaired in individuals with various autoimmune diseases. Primary biliary cholangitis (PBC), an autoimmune disease, clinically presents as chronic cholestasis and nonsuppurative destructive cholangitis. A role for CD19 + CD24 hi CD38 hi B cells in PBC is unknown. This study investigated the frequency and functional variation of circulating CD19 + CD24 hi CD38 hi B cells in PBC patients. Flow cytometry was employed to quantify the percentage of CD19 + CD24 hi CD38 hi B cells in peripheral blood samples. Correlations between CD19 + CD24 hi CD38 hi B cells and routine laboratory parameters were assessed. Levels of IL-10, TNF- α, IL-6 and IL-12, and Tim-1 in CD19 + CD24 hi CD38 hi B cells from PBC patients were analyzed. The effect of CD19 + CD24 hi CD38 hi B cells on CD4 + T cell differentiation was evaluated. The percentage of CD19 + CD24 hi CD38 hi B cells in PBC patients was significantly higher than in healthy controls and was positively correlated with liver cholestasis. After activation by anti-B cell receptor and CpG, the production of IL-10 was decreased and the production of IL-6 and IL-12 was increased in CD19 + CD24 hi CD38 hi B cells from PBC patients. Moreover, Tim-1 levels were significantly downregulated in CD19 + CD24 hi CD38 hi B cells from PBC patients. Coculture showed that PBC-derived CD19 + CD24 hi CD38 hi B cells were less capable of CD4 + T cell inhibition, but promoted Th1 cell differentiation. In conclusion, PBC patients have expanded percentages, but impaired CD19 + CD24 hi CD38 hi B cells, which correlate with disease damage. In PBC patients, this B cell subset has a skewed proinflammatory cytokine profile and a decreased capacity to suppress immune function, which may contribute to the pathogenesis of PBC.